Implementasi Program Antikorupsi di Kalangan Mahasiswa dan Masyarakat Berbasis Pancasila di Car Free Day (CFD) Pekanbaru - Fauroka, Zahwa; Sulistianingrum, Eka; Candra, Delia; Fadhillah, Hanifa; Ramadhani, Siti Syarah; Putri, Yolanda; Maharani, Suci Gina; Safariah, Wan (Educationist: Journal of Educational and Cultural Studies, 2025)
Indonesia, as a country based on law with Pancasila and the 1945 Constitution as its foundation, prioritizes the democratic principle "from the people, by the people, and for the people." Law plays a crucial role in creating social order and ensuring justice. However, a major issue threatening the stability of the country is corruption, which undermines the core values of Pancasila and hinders development. Data from Transparency International (2023) shows a concerning Corruption Perception Index for Indonesia, while the KPK report (2022) reveals the detrimental effects of corruption on the economy and societal morals. Therefore, anti-corruption education is vital, with a focus on the younger generation as agents of change. Anti-corruption education aims to shape character and moral awareness in combating corruption. Pancasila, as the state foundation, should be used as a basis for the formulation of anti-corruption education regulations. This research aims to campaign for anti-corruption values based on Pancasila to students and the public through activities such as Car Free Day (CFD) in Pekanbaru City. Through direct interaction between students and the community, anti-corruption values can be creatively disseminated, raising public awareness of the importance of fighting corruption and building a better national character.